Aspectos da representação do território paulista em sua cartografia impressa: uma análise cartobibliográfica (1833-1932) - José Rogério Beier; Daniel Marhtin (Confins)
The field of historical cartography has been widely developed over the past 30 years, with an increasing number of works using historical maps as sources for understanding the processes of the social and economic history of a place at a given time. Yet, even today, many works produced by historians still relegate maps to a lower category of documents or, worse, still, use them only as an illustration or in a very punctual way, usually linked to the location or the topography of the space considered. The main object of this paper is to analyze cartographic representations produced in the territory of the province of São Paulo between 1833 and 1932, aiming to explicit how, using techniques related to the history of cartography, maps can be used as sources to produce interpretations of the processes of the social, cultural and economic history of the society which produced them.